Microglia and Spinal Cord Synaptic Plasticity in Persistent Pain - Sarah Taves; Temugin Berta; Gang Chen; Ru-Rong Ji (Neural Plasticity)
Microglia are regarded as macrophages in the central nervous system (CNS) and play an important role in neuroinflammation in the CNS. Microglial activation has been strongly implicated in neurodegeneration in the brain. Increasing evidence also suggests an important role of spinal cord microglia in the genesis of persistent pain, by releasing the proinflammatory cytokines tumor necrosis factor-alpha (TNFα), Interleukine-1beta (IL-1β), and brain derived neurotrophic factor (BDNF). In this review, we discuss the recent findings illustrating the importance of microglial mediators in regulating synaptic plasticity of the excitatory and inhibitory pain circuits in the spinal cord, leading to enhanced pain states. Insights into microglial-neuronal interactions in the spinal cord dorsal horn will not only further our understanding of neural plasticity but may also lead to novel therapeutics for chronic pain management.